How to manage collaboration among engineering schools, technical universities and engineering employers through a field experience course technology; Man in India - Morozova M. V. Marina Vyacheslavovna; Paljyanov M. P. Mikhail Pavlovich; Sinenko V. Ya. Vasily Yakovlevich; Rudneva E. L. Elena Leonidovna; Kasatkina N. E. Nataljya Emiljevna
Title screen